POTENCY OF EEL Anguilla marmorata in NORTH LOMBOK REGENCY, WEST NUSA TENGGARA PROVINCE - Setyono, Bagus Dwi Hari; Junaidi, Muhammad; Marzuki, Muhammad; Paryono, Paryono; Azhar, Fariq (AQUASAINS, 2018)
Anguilla spp. is one of the ï¬sheryÂ commodities that have high economic value.North Lombok regency is one of the centralÂ part of Indonesia which is suspected to haveÂ potential as an eel migration route. This studyÂ aims to obtain information about the identiï¬cationÂ of Anguilla spp ï¬sh populations. in NorthÂ Lombok Regency. The results showed that theÂ waters area of North Lombok Regency has theÂ potential of eel ï¬sh source Anguilla marmorata.Â The timing of eel migration is still unknown, soÂ further research is needed which will cover aÂ full year.